Penempatan Tenaga Kerja Asing di Proyek X berdasarkan Undang-Undang Nomor 11 Tahun 20 tentang Cipta Kerja dihubungkan dengan Prinsip Alih Teknologi - Tikko Reza Pahelvi; Rini Irianti Sundary (UNISBA Press, 2021)
Abstract. The use of foreign workers in Indonesia is the most important thing for the advancement of a company that implements the use or employs foreign workers. The use of foreign workers itself is not an ordinary thing, but something that must be maintained, because the entry of foreign workers into Indonesia can have a positive impact on economic growth. On the other hand, the use of Foreign Workers can also have a negative impact if the placement of Foreign Workers is not carried out based on the laws and regulations that have been made by the relevant government. One of the purposes of using foreign workers (TKA) is to transfer technology and transfer skills that have not been implemented properly.